2017
DOI: 10.1002/slct.201700457
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3-Substituted Quinazolinones via C-N and C-C bond Cleavage of Enaminone

Abstract: A general and efficient TsOH mediated reaction of o-aminobenzamides with enaminone via CÀN and CÀC bond cleavage leading to quinazolinones has been achieved. This strategy involves CÀN/CÀC bond cleavage and CÀN bond formation in a single operation. Highlight of this work is associated metal free, peroxide free and base free reaction condition. All the synthesized compounds were characterized by NMR and ESI-MS spectral studies.[a] S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Next, the influence of temperature on this reaction was investigated, reacting at 100 °C the yield of desired product up to 82% (Table 1, entries 7-10). Through an investigation of the amount of catalyst, we found that the yield of the target product did not reduce even the amount of catalyst decreased to 10 mol% (Table 1, entries [11][12]. Various oxidants such as TBHP, DTBP, H 2 O 2 , Na 2 S 2 O 8 , (NH 4 ) 2 S 2 O 8 were examined, we observed that TBHP was the most efficient one (entries 11, 13-17).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Next, the influence of temperature on this reaction was investigated, reacting at 100 °C the yield of desired product up to 82% (Table 1, entries 7-10). Through an investigation of the amount of catalyst, we found that the yield of the target product did not reduce even the amount of catalyst decreased to 10 mol% (Table 1, entries [11][12]. Various oxidants such as TBHP, DTBP, H 2 O 2 , Na 2 S 2 O 8 , (NH 4 ) 2 S 2 O 8 were examined, we observed that TBHP was the most efficient one (entries 11, 13-17).…”
Section: Resultsmentioning
confidence: 96%
“…[6] Among these synthetic strategies, the one in which o-aminobenzamides proceed in an oxidative dual amination of sp 3 CÀ H bonds is probably the most typical one. Under this synthetic strategies, aromatic benzyl sp 3 CÀ H bond like toluene and heterocyclic analogues, [7] acetophenone, [8] dicumyl peroxide, [9] TBHP, [10] enaminones, [11] CO 2 , [12] alcohols, [13] isocyanides [14] and alkyl acetoacetates [15] etc. [16] has been utilized as one-carbon sources to react with o-aminobenzamides under both metalmediated and metal-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous starting materials have been used in the previously reported literature for the synthesis of quinazolinones, among which 2-amino benzamide serves as one prominent substrate . Additionally, many different techniques have been developed to produce annulation products from the common substrate 2-amino benzamide. , A transition metal-assisted and metal-free synthesis technique has been devised in response to the need for a specific derivative with a certain functional group. , Besides this, some of the developed synthetic routes are restricted to a metal approach which is a major problem for pharmaceutical preparations due to the presence of its impurities in the final desired product .…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our ongoing research to develope new routes for the construction of various heterocyclic systems, 21 we investigated the reaction of 4-methylacetophenone 1b with 2-(1 H -benzo[ d ]imidazol-2-yl) aniline 2 as model substrates for the present study. The reaction has been carried out under various reaction conditions, as depicted in Table 1.…”
Section: Introductionmentioning
confidence: 99%